The effect of solar geometry on a window shade for energy efficient design of building - Rafidah, Saidin (2013)
This report is based on the effect of solar geometry on a window shade for energy efficient design of building. The objective of this project is investigate the effect of the solar geometry on a window shade of different aspect for energy efficiency purposes and to investigate the effect of using horizontal window shade in reducing solar radiation, thus improving the energy efficiency. It is important to understand the science of solar geometry, it is very important in determining and simulates shadows emitted by solar shades, and directly overhanging horizontal windows to block part of the s radiation will penetrate into the space available in room. Indirectly, the shadow appears to the solar colour varies according to solar geometry, although the movement of the sun relative to the earth's constant. The method that have used in this project is using the C++ Programming to calculate the declination angle and construct diagram to do the sun path. Then, the AWSHADE 3.0 is used to calculate and get the shading degree or beam degree. It was founded, the horizontal shading is suitable to use in highest latitude like Perlis because the radiation arising from the solar movement and the effect caused the solar geometry on the window shades